2004
DOI: 10.1093/rheumatology/keg477
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bisphosphonate treatment in patients with Paget's disease of the skull

Abstract: HRCT imaging is a well suited tool for demonstrating the complication of Paget's disease. QBS and measurement of serum tAP level may also be regarded as useful techniques for monitoring treatment. However, hearing may remain impaired in spite of the improved scintigraphy and laboratory parameters, therefore, audiometric assessment is also important in pagetic patients with skull involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 22 publications
0
10
0
3
Order By: Relevance
“…The authors reported no significant change in hearing thresholds after 12 months overall, although they commented that there was a nonsignificant (7.5 db) increase in hearing thresholds in the high-frequency region in those with sensorineural loss. (102) The evidence summary and recommendations for the use of bisphosphonates to prevent progression of hearing loss in PDB are shown in Table 11.…”
Section: Progression Of Hearing Lossmentioning
confidence: 99%
“…The authors reported no significant change in hearing thresholds after 12 months overall, although they commented that there was a nonsignificant (7.5 db) increase in hearing thresholds in the high-frequency region in those with sensorineural loss. (102) The evidence summary and recommendations for the use of bisphosphonates to prevent progression of hearing loss in PDB are shown in Table 11.…”
Section: Progression Of Hearing Lossmentioning
confidence: 99%
“…It is characterised by an increase in (Donáth et al, 2004) resulting in the increased formation of osteoid that is softer and weaker than normal (Kanis, 1998). Present in approximately 3-4% of the population (Resnick, 1988) and most common in males (Roches et al, 2002) over the age of 40 years (Davie et al, 1999), Paget's disease generally affects two or more bones (Schneider et al, 2002).…”
Section: Paget's Disease Of Bonementioning
confidence: 99%
“…This is especially likely when clinical presentation of the disease includes a neurologic deficit in addition to the bony narrowing of the IAC, as in the present case and as seen also in patients with hyperostotic conditions of the skull. 9,10 Long-term followup after cochlear implantation is mandatory to better predict outcomes of future cases and to gain more informed insight on how to maximize postimplantation performance in patients with Paget's disease.…”
Section: Commentsmentioning
confidence: 99%